Rectal Foreign Body Causing Perforation: A Case Report - Shrestha, Nischal; Belbase, Narayan Prasad; Bhujel, Sushim; Khatiwada, Sagar; Timilsina, Binaya; Koirala, Nishnata (Journal of College of Medical Sciences-Nepal, 2023)
The rectal foreign body is a rare presentation with rising incidence. We present a case of a 26-year-old heterosexual male with an alleged history of sexual assault with insertion of a large foreign body through the anus two days prior with peritonitis. After investigations, the patient underwent an exploratory laparotomy, foreign body removal, primary repair of perforation with a diverting colostomy. Diversion must be considered in cases where the extent of anal sphincter mechanism injury is in question. The patient had a good outcome. Assessment of the shape, size, nature, and location of the object through appropriate imaging is necessary. Exploratory laparotomy is inevitable in cases of perforation.